Trends in multidrug-resistant tuberculosis in Tehran, Iran: an analysis of published data - Nasiri, Mohammad Javad; Heidary, Mohsen; Goudarzi, Hossein; Tabarsi, Payam (German Medical Science GMS Publishing House, 2019)
Introduction: Multidrug-resistant tuberculosis (MDR-TB) is one of the major public health threats especially in developing countries. In Iran, the emergence and spread of MDR-TB are likely to pose a significant problem for the National Tubeculosis Control Program (NTP). In this study, to determine the trend of MDR-TB in Tehran, the results of published studies were analyzed.Methods: Several databases were searched, including Medline, Embase, Web of Science and Iranian databases. Studies which report the preva of MDR-TB by World Health Organization (WHO)-endorsed drug susceptibility testing (DST) methods were included in the study. Data were analyzed with SPSS 20 (SPSS, Chicago, Illinois, USA).Results: Analysis of the MDR-TB trend did not show any increase among new TB cases, but the trend of MDR-TB was significantly increased among previously treated cases. The prevalence of MDR-TB from 48.0% in 1996 reached 58.0% in 2004 (P<0.05). Conclusions: Our analysis shows an increasing trend in MDR-TB, parlarly in retreatment cases. This study strongly highlights the need to develop further strategies for surveillance, monitoring, and management of MDR-TB cases.